2019
DOI: 10.1002/pro.3775
|View full text |Cite
|
Sign up to set email alerts
|

Identification of FAM181A and FAM181B as new interactors with the TEAD transcription factors

Abstract: The Hippo pathway is a key signaling pathway in the control of organ size and development. The most distal elements of this pathway, the TEAD transcription factors, are regulated by several proteins, such as YAP (Yes‐associated protein), TAZ (transcriptional co‐activator with PDZ‐binding motif) and VGLL1‐4 (Vestigial‐like members 1–4). In this article, combining structural data and motif searches in protein databases, we identify two new TEAD interactors: FAM181A and FAM181B. Our structural data show that they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 40 publications
0
44
1
Order By: Relevance
“…We also repeatedly observed that the expression levels of FLAG-tagged VGLL2 were significantly higher in co-transfection experiments performed with TEAD4 proteins (Fig 4). In contrast to our previously reported observations for FAM181A (Bokhovchuk, Mesrouze et al, 2020), this effect happened with wild-type and mutant forms of TEAD4 and VGLL2, suggesting a the formation of a complex formation between these two proteins. This is presumably mediated through the interactions taking place at the β-strand:αhelix binding site, which are unaffected by the Asp272Ala TEAD4 or the deletion of the Ω-loop and may enhance the stability of co-overexpressed VGLL2 in this experimental setting.…”
Section: Presence Of An ω-Loop In Other Proteins Of the Vg/vgll1-3 Sucontrasting
confidence: 99%
See 1 more Smart Citation
“…We also repeatedly observed that the expression levels of FLAG-tagged VGLL2 were significantly higher in co-transfection experiments performed with TEAD4 proteins (Fig 4). In contrast to our previously reported observations for FAM181A (Bokhovchuk, Mesrouze et al, 2020), this effect happened with wild-type and mutant forms of TEAD4 and VGLL2, suggesting a the formation of a complex formation between these two proteins. This is presumably mediated through the interactions taking place at the β-strand:αhelix binding site, which are unaffected by the Asp272Ala TEAD4 or the deletion of the Ω-loop and may enhance the stability of co-overexpressed VGLL2 in this experimental setting.…”
Section: Presence Of An ω-Loop In Other Proteins Of the Vg/vgll1-3 Sucontrasting
confidence: 99%
“…At the end of the simulation, the linker region converged towards a loop conformation with no regular secondary structure that appeared stabilized by an aromatic stacking interaction between residues Tyr115 VGLL2 and Phe196 VGLL2 . All other cellular biology tools and methods, namely TEAD4 constructs and coimmunoprecipitations, were essentially as described previously (Bokhovchuk et al, 2020, Mesrouze et al, 2017a. NGS-PBT for 1 h. Samples were then incubated in primary antibody diluted in blocking solution over-night.…”
Section: Cloning Expression and Purification Of The Proteins For Thementioning
confidence: 99%
“…The pcDNA3.1 Hygro-DEST_VGLL2_Ω_loop mutant was generated by use of the QuikChange Lightning Site-Directed Mutagenesis kit (Stratagene, San Diego, CA), with oligo 5′ CCC TTG GAG AGA CTG CAG CTT CTA TCA GGC TCC TGT GCC 3′ (removing amino acid positions 134–149) and the sequence of resulting cDNA clones verified. All other cellular biology tools and methods, namely TEAD4 constructs and co-immunoprecipitations, were essentially as described previously 30 , 50 . The inter-experimental reproducibility across the co-IP experiments appeared less robust in the wild-type HEK293FT (i.e.…”
Section: Methodsmentioning
confidence: 99%
“…Several residues of the Ω‐loop region are well conserved (Figures 1c and 2). Zhang et al have suggested that Val84 Hs at the N‐terminus of the Ω‐loop has a shielding effect on the folding of this region 24 and the presence of this residue dramatically increases the affinity of peptides mimicking the Ω‐loop of YAP 23 . Val84 Hs is often replaced by a leucine and in some cases by an isoleucine or a lysine.…”
Section: Resultsmentioning
confidence: 99%
“…This residue is quite well conserved, but in a few sequences it is replaced by a tryptophan. It has been shown that the presence of a larger aromatic residue at position‐96 Hs (e.g., 1‐naphtylalanine) enhances the affinity of YAP 30 and that FAM181A, which also binds to TEAD via an Ω‐loop, contains a tryptophan at this position 23 . Phe96 Hs also makes a π‐cation interaction with Arg87 Hs , and this interaction is thought to contribute to the stabilization of the bound Ω‐loop (Figure 1c).…”
Section: Resultsmentioning
confidence: 99%